Strategic Management of Increasing Competency of Students Through Strengthening Character Education (PPK) and School Literation Movement (GLS) at Muhammadiyah Junior High School Margasari - Rohmayanti, Lilis (International Conference of Moslem Society, 2019)
Strengthening Character Education (PPK) and the School Literacy Movement (GLS) are two very important movements in the world of education today. Both are movements that can improve Student Competence in both attitudinal, knowledge and skills competencies. The purpose of this study is to describe the process or stages of strategic management in the form of Scanning, Formating, Implementing and Evaluating in PPK and GLS at Muhammadiyah Margasari Middle School in Tegal Regency. This study uses qualitative research. Data analysis methods used are (1) Data Collection (2) Data Reduction (3) Data Display (4) Conclusion Drawing / Verification. The results of this study are Muhammadiyah Margasari Middle School implementing the stages of strategic management in PPK and Literacy. The stages are First, Scanning includes External and Internal Environmental Analysis with SWOT Analysis. Second, Formating through (1) Formulation of Vision, Mission, Core Value (2) Formulation of integrated School Objectives in PPK and Literacy (3) Formulation of Short and Medium Term School Strategic Plans that contain strategic programs, targets, strategies, funds and resources to improve competency of students through Strengthening Character Education (PPK) and School Literacy Movement (GLS), indicators of success. Third, Implementing is the implementation of improving the quality of students through PPK and Literacy activities including (1) PPK based on class, school and community. (2) GLS habituation, learning and development. Fourth, Evaluating is an evaluation of activities that have been carried out through School Self Evaluation for follow-up and continuous improvement.